Baseline carotid intima-media complex echogenicity associates with the 3-year progression of intima-media thickness. (11th May 2022) - Nyman, E; Liv, P; Wester, P; Naslund, U; Gronlund, C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Region Vasterbotten Central ALF and the Swedish Research Council Background: Echogenicity of the intima-media (IM) complex and progression of carotid intima media thickness (cIMT) have both separately been demonstrated to predict cardiovascular disease (CVD). However, it is unknown if the IM echogenicity reflects arterial wall remodelling associated with increased progression of cIMT. Purpose: The aim of this study was to evaluate if the baseline echogenicity of the IM-complex measured by ultrasound is associated with cIMT progression over a 3-year follow-up period. Methods: Ultrasound images from baseline and 3-year follow-up performed for the randomised controlled trial 'Visualization of asymptomatic atherosclerotic disease for optimum cardiovascular prevention' (VIPVIZA) were included in this study (n: 3154). Participants were 40, 50 or 60 years old at baseline and had at minimum one traditional risk factor for CVD to be included in the VIPVIZA study. Measurements of mean cIMT were made at baseline and in the 3-year follow-up in the distal 1 cm of the common carotid artery at standardised angles bilaterally. Echogenicity of the IM-complex was determined by greyscale median (IM-GSM), automatically calculated from the B-mode ultrasound images. Associations between IM-GSM at baseline and the 3-year progression of cIMT were investigated using linear regression models, and stratified by sex, age and VIPVIZA study group (intervention versus control). In addition, adjusted analysis for traditional risk factors was also performed. All analysis was carried out on left and right sides separately. Results: The unadjusted analysis showed associations between baseline IM-GSM with the 3-year progression of cIMT (p<0.001 for both left and right sides, Figure 1). The association between IM-GSM and cIMT was statistically significant bilaterally in both male and female participants and on comparison of VIPVIZA study subgroups. When stratifying by age group, the association between baseline IM-GSM and cIMT progression was present among 40 (p<0.001) and 60 year olds (p<0.001), but not among 50 years old (p=0.906) in the left side. In the right CCA the association was significant among 40 years old (p=0.047), but not for 50 and 60 years (p=0.106 and 0.067, respectively). Adjustments for traditional risk factors did not alter the estimated relationship between baseline IM-GSM and 3-year cIMT progression. Conclusion: Baseline ultrasound echogenicity of the IM-complex is associated with the 3-year progression of cIMT among a middle-aged population with subclinical atherosclerosis. Echogenicity of the IM-complex may serve to identify arterial wall remodelling reflecting progressive atherosclerotic disease and could be a valuable tool in future CVD prevention.